Dnevna bolnišnica - Kunčič Mandelc, Judita (Medicinski razgledi, 2005)
The beginnings of outpatient surgical activities performed under general anesthesia date back to the early years of the twentieth century. In the 1980's, interest in this activity was revived also because newer anesthesia techniques enabled high-quafity and cost-efficient care of surgical outpatients. The advantages of these activities include the smallest possible interference with the rhythm of everyday life of the patients undergoing surgery at a day clinic, reduced risk of hospital infections among surgical patients and better management of daily care costs. Organisation of a surgicalday clinic at the Jesenice General Hospital was a major and complicated organisational and professional undertaking, which had a single goal: to ensure high-quality and safe patient health care. Along with the provision of appropriate premises and equipment, and careful monitoring of patients using clinical paths, daily adjustment of activities to the set goalswas also necessary. The evaluation of results achieved after one year of operation comprised an organisational, medical and economic evaluation, along with the evaluation of patient satisfaction and satisfaction of the day clinicstaff. In spite of positive results, new challenges and tasks are arising, which are related to further improvement of the quality of patient care.
Keywords: Ambulatory Surgery; Anestezija; Day Care; Dnevna oskrba; Anesthesia; Pooperativne komplikacije; Postoperative Complications; Medicinske kartoteke; kirurško zdravljenje; Medical Records; ambulantna kirurgija; organizacija zdravstva